The Influence of Mental Health on Quarter Life Crisis in the Emerging Adulthood Phase - Nasya, Vania Azariya; Amelasasih, Prianggi (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2025)
The transition from adolescence to early adulthood is a critical developmental phase that involves identity exploration, independence, and the pursuit of life goals. During this stage, individuals are often confronted with academic demands, social expectations, and uncertainty about the future, which can trigger emotional distress. This study examines the influence of mental health on the occurrence of quarter-life crisis among individuals in the emerging adulthood phase (18–29 years old). Using a quantitative descriptive approach, the research focuses on the relationship between mental well-being and symptoms such as future anxiety, self-doubt, and dissatisfaction with life. The findings indicate that mental health has a significant impact on an individual’s ability to cope with challenges and adapt to life transitions. Those with stable mental health show greater resilience, better decision-making, and lower vulnerability to quarter-life crisis, whereas those with poor mental health are more prone to confusion, overthinking, and pessimism about personal and professional goals. The results highlight the importance of mental health education, preventive interventions, and counseling services to help young adults manage emotional stress and navigate transitions effectively.